English Pre-service Teachers’ Perceptions on the Role of Microteaching in the Teaching Practice Program - Vella Dwi Rahayu; Indah Tri Purwanti; Mahdum Mahdum (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study investigated the perceptions of English preservice teachers at Universitas Riau regarding the role of microteaching in preparing them for the teaching practice program. Microteaching is a fundamental element of teacher education, designed to develop essential pedagogical competencies prior to real classroom teaching. An explanatory sequential mixed-method design was employed, beginning with a survey of 64 eighth-semester preservice teachers and followed by interviews with six purposively selected participants who reflected both positive and critical perspectives. The 19-item questionnaire demonstrated high reliability (Cronbach’s Alpha = 0.859). Quantitative findings indicated that preservice teachers perceived microteaching as highly beneficial across four domains: lesson planning (M = 3.9), lesson preparation (M = 3.8), teaching skills (M = 3.9), and self-confidence (M = 3.9). These results were supported by interview data, which highlighted that microteaching facilitated systematic lesson design, encouraged interactive pedagogical techniques, and strengthened confidence in classroom delivery. At the same time, participants also reported challenges, including classroom management difficulties, limited authenticity of simulations, lack of supervision, time constraints, and anxiety in transitioning to actual classrooms. Overall, the study suggested that microteaching is an effective preparatory stage; however, its impact was constrained by the gap between simulated practice and real classroom contexts. Despite limitations related to sample size, this study contributed to teacher education discourse by underscoring the pedagogical value of microteaching and recommending curriculum refinement, mentorship, and greater integration of authentic classroom experiences.